Schooled - Korman, Gordon (New York : Hyperion Books for Children, 2007)
Homeschooled by his hippie grandmother, Capricorn (Cap) Anderson has never watched television, tasted a pizza, or even heard of a wedgie. But when his grandmother lands in the hospital, Cap is forced to move in with a guidance counselor and attend the local middle school. While Cap knows a lot about tie-dyeing and Zen Buddhism, no education could prepare him for the politics of public school.
Keywords: Middle school students -- Juvenile fiction; Home schooling -- Juvenile fiction